Fuzzy-based modeling and speed optimization of a centrifugal blood pump using a modified and constrained Bees algorithm - Incebay, Omer; Onder, Ahmet; Arif Sen, Muhammed; Yapici, Rafet; Kalyoncu, Mete (Computer methods and programs in biomedicine, 2022)
•The Bees algorithm is proposed for the first time to determine the optimal speed of a blood pump by modifying and adding constraints.•A meta-heuristic approach method to obtain optimum blood pump rotational speed with design criteria of the blood pump.•Fuzzy logic based modelling of blood pumps with results from CFD simulations. Side effects that may occur when using blood pumps for treatment of patients are the main limitations on pump rotational speed determination. Efforts are being made to reduce side effects in both design and usage procedures. In determining the pump speed for treatment, decreasing the pressure on the main artery and preserving the valve functions are taken into consideration. In addition to these, the parameters considered for design which include pump efficiency and mechanical effects on blood cells, should also be taken into consideration. In this study, the aim is to obtain the optimum pump speed for the maximum hydraulic efficiency and minimum wall shear stresses that occur inside the pump. Blood pump modeling based on fuzzy logic is created on the hydraulic performance data of a centrifugal blood pump, whose design, CFD analysis, manufacture and experimental testing have been performed previously. Using this fuzzy logic model, the optimum pump speeds were determined using the Bees Algorithm, an intuitive optimization algorithm, in the operating range 1-7 L/min fluid flow rate. In the optimization process, the aim is to achieve minimum shear stress with maximal efficiency. Intravascular pressure limits (90-160 mm-Hg) were set as pressure constraints. The optimum operating point is obtained as a 3350 rpm pump speed and a 4.35 L/min flow rate. At this operating point, CFD simulation is performed, and maximum wall shear stress was found to be 1458 Pa and its efficiency as 34.2%. In addition to the parameters commonly used in the pump speed optimization of blood pumps, the use of wall shear stresses and pump efficiency can provide certain improvements.